THE EFFECT OF LOCATION, FACILITIES, AND PRICE ON BOARDING HOUSE TENANT SATISFACTION IN SLEMAN (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
This study aims to analyze the influence of location, facilities, and price on the satisfaction of boarding house tenants in Sleman Regency, Yogyakarta Special Region. The study was conducted using a quantitative approach and survey method on 97 boarding house tenant respondents. The independent variables in this study were location, facilities, and price, while the dependent variable was boarding house tenant satisfaction. Data analysis was performed using multiple linear regression using SPSS software. The results showed that all three, namely: location, facilities, and price, have a significant effect on boarding house tenant satisfaction. This study provides practical implications for boarding house owners in improving marketing strategies and service quality to achieve tenant satisfaction and loyalty.
Keywords: location; facilities; price; tenant satisfaction; boarding house